Hybrid template directed hydrothermal synthesis of MCM-41 silicas with surface silanol and 3-chloropropyl groups - N. V. Roik; I. M. Trofymchuk; L. O. Belyakova; O. I. Oranska (Хімія, фізика та технологія поверхні)
Silicas of MCM-41?type with reactive functional groups are widely used as starting substrates in large variety of post?synthetic chemical modification pathways. Therefore, variation of their structural characteristics in the process of templated sol?gel synthesis or post-synthetic treatment is of great importance. The aim of this work was to elucidate the influence of template agent selection on structural features of MCM-41?type materials with surface silanol and 3?chloropropyl groups. For this purpose, template-assisted sol-gel condensation of structure forming silanes (tetraethyl orthosilicate and 3?chloropropyltriethoxysilane) was carried out in the presence of decyltrimethylammonium bromide as structure-directing agent. The capability of cyclic oligosaccharide                          (?-cyclodextrin) to interact with surfactant micelles in the process of hydrothermal sol-gel synthesis and to influence the formation of mesoporous structure of silica materials was studied. The IR spectroscopy was applied to carry out control under the complete removal of template moieties from pores by extraction procedure and to confirm introduction of 3?chloropropyl groups into the surface layer of synthesized silicas. Arrangement of mesoscale pores and structural parameters were estimated from the results of X?ray diffraction and low-temperature adsorption-desorption of nitrogen. It has been found that ??cyclodextrin as component of hybrid template has positive effect on porous structure of 3-chloropropyl-functionalized MCM-41-type silica causing increase of surface area accompanied with preservation of pore ordering. Moreover, both ionic surfactant and oligosaccharide components of hybrid template act as porogens during sol-gel condensation of structure forming silanes enable to prepare silica materials with micro-mesoporosity. Proposed approach can be useful in synthesis of MCM?41?type silicas with surface linker groups and controlled structural characteristics (pore size, geometry and ordering), which have great potential as substrates in design of sophisticated materials.